Actividades de la unidad de producción del hato bovino ESPAM MFL y la calidad ambiental del entorno - Menéndez Solórzano, Adriana Valeria (2015)
A study on the effect of ranching and the residue concentration of livestock activities may have on the environment is presented. This study was conducted to evaluate the activities of the production unit Cattle Herd ESPAM of MFL in the quality of the environment, for which the bibliographic and descriptive methods in order to assess the impact of these activities were used. an interview with the personnel of the farm was carried out and the GIS tool was used through the Arc GIS software to get maps of the study area. The results indicate that the process can be defined in three phases: feeding, milking and milk transport. The cattle feed on grass Savoie (Panicum maximum) and Star (Cynodon nlemfuensis). Cattle milking it done manually in the morning (5:30 am) daily, the production obtained is 125 liters / day obtained from 18 cows that are under production, with an average production of 5.12 l / ha and / or 6.94 l / veal individual. Regarding the quality of the environment two samples both soil and water were taken, which sample A soil exceed the limits in the parameters of phosphorus and organic matter. Therefore it is proposed in the management plan, mitigation measures to measure the concentration levels of P, K and MO, and the socialization of the construction of a digester as an alternative to seize control animal excreta.